Empirical Modeling of Lithium-ion Batteries Based on Electrochemical Impedance Spectroscopy Tests. (1st April 2015) - Samadani, Ehsan; Farhad, Siamak; Scott, William; Mastali, Mehrdad; Gimenez, Leonardo E.; Fowler, Michael; Fraser, Roydon A.
Highlights: Two commercial Lithium-ion batteries are studied through HPPC and EIS tests. An equivalent circuit model is developed for a range of operating conditions. This model improves the current battery empirical models for vehicle applications This model is proved to be efficient in terms of predicting HPPC test resistances. ABSTRACT: An empirical model for commercial lithium-ion batteries is developed based on electrochemical impedance spectroscopy (EIS) tests. An equivalent circuit is established according to EIS test observations at various battery states of charge and temperatures. A Laplace transfer time based model is developed based on the circuit which can predict the battery operating output potential difference in battery electric and plug-in hybrid vehicles at various operating conditions. This model demonstrates up to 6% improvement compared to simple resistance and Thevenin models and is suitable for modeling and on-board controller purposes. Results also show that this model can be used to predict the battery internal resistance obtained from hybrid pulse power characterization (HPPC) tests to within 20 percent, making it suitable for low to medium fidelity powertrain design purposes. In total, this simple battery model can be employed as a real-time model in electrified vehicle battery management systems.